2019
DOI: 10.1093/rheumatology/kez160
|View full text |Cite
|
Sign up to set email alerts
|

Effect of probiotics on gastrointestinal symptoms and immune parameters in systemic sclerosis: a randomized placebo-controlled trial

Abstract: Objectives Changes in the intestinal microbiota have been associated with the pathogenesis of SSc. Probiotics act by modulating the microbiome and the immune response. This study aimed to evaluate the efficacy of probiotics on gastrointestinal (GI) symptoms and immune responses in SSc patients. Methods Patients with SSc with a moderate–severe total score on the University of California Los Angeles Scleroderma Clinical Trials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 18 publications
0
32
0
Order By: Relevance
“…An RCT including 73 patients, receiving either probiotics (n = 37) or placebo (n = 36), evaluated the efficacy of probiotics on GI symptoms and immune responses in SSc patients. 36 After 8 weeks, no difference in the UCLA GIT 2.0 score between the two groups was observed, but the probiotic group showed a significant decrease in the proportion of Th17 cells compared with placebo. No severe side-effects were observed in this study.…”
Section: New Approaches To Therapymentioning
confidence: 83%
See 1 more Smart Citation
“…An RCT including 73 patients, receiving either probiotics (n = 37) or placebo (n = 36), evaluated the efficacy of probiotics on GI symptoms and immune responses in SSc patients. 36 After 8 weeks, no difference in the UCLA GIT 2.0 score between the two groups was observed, but the probiotic group showed a significant decrease in the proportion of Th17 cells compared with placebo. No severe side-effects were observed in this study.…”
Section: New Approaches To Therapymentioning
confidence: 83%
“…No severe side-effects were observed in this study. 36 Of note, there have been some concerns regarding the safety of probiotic use in immunocompromised patients developing life-threatening pneumonia, endocarditis, and sepsis due to some probiotic strains becoming opportunistic pathogens. 37 To our knowledge, there are no reports regarding safety issues associated with probiotic use in SSc patients to date.…”
Section: New Approaches To Therapymentioning
confidence: 99%
“…[ 29 ] Recently, the pathogenesis of SSc has been reported to be related to the dysbiosis of gut microbiota. [ 30 , 31 ] Though there are several issues to be understood, FMT has been as an innovative approach to SSc. [ 32 ] However, as far as we know,no literature review systematically assesses the efficacy and safety of FMT in the treatment of SSc.…”
Section: Discussionmentioning
confidence: 99%
“…As far as SSc is concerned, some RCTs have been carried out only in patients with gastrointestinal involvement. One of these has shown that an 8-week probiotics supplementation did not have any effect in reducing gastrointestinal symptoms but lead to a decrease in Th17 cell levels indicating an immunomodulatory capacity of the probiotic strains used ( Table 1) (17). Another trial confirmed the inefficacy of probiotics in systemic sclerosis associated gastrointestinal disease but SSc clinical outcomes were not addressed in that study (30).…”
Section: Other Rheumatic Diseasesmentioning
confidence: 96%